5
$\begingroup$

Does there exist an operator, $\star$, such that for all full rank matrices $B$ and all $A$ of appropriate dimensions: $$ B(B^\intercal AB)^\star B^\intercal = A^\star, $$ and such that $A^\star=0$ if and only if $A=0$?

Edit: Also, $\star : \operatorname{M}(m,n,\mathbb R) \to \operatorname{M}(n,m,\mathbb R)$.

Edit: If possible, we would also like $\operatorname{rank}(A^\star)=\operatorname{rank}(A)$.

$\endgroup$
  • $\begingroup$ See Moore-Penrose pseudoinverse $\endgroup$ – მამუკა ჯიბლაძე May 17 '17 at 19:59
  • $\begingroup$ @მამუკაჯიბლაძე Moore-Penrose pseudoinverse does not satisfy this. For example, if B=[1 1; 1 2] and A = [1 0; 0 0]. $\endgroup$ – PThomasCS May 17 '17 at 20:44
  • 2
    $\begingroup$ If $B^T A B$ makes any sense, $A$ must be a square matrix. $\endgroup$ – Robert Israel May 17 '17 at 21:40
  • $\begingroup$ @RobertIsrael Yes, $A$ must be square. If it helps, we can even assume that $A$ is symmetric. $\endgroup$ – PThomasCS May 17 '17 at 22:12
  • $\begingroup$ So why did you say $\star \;: M(m,n, \mathbb R) \to M(n,m,\mathbb R)$? $\endgroup$ – Robert Israel May 17 '17 at 22:48
7
$\begingroup$

No. We suppose it is defined for $2\times 2$ matrices and we get a contradiction. Unless you drop the requirement on $\operatorname{rank} A^\star$ in which case $A^\star=0$ trivially works.

Let $A=\begin{pmatrix} 1 & 0 \\ 0 & 0\end{pmatrix}$ and let $B=\begin{pmatrix} a & b\\ c & d\end{pmatrix}$ with arbitrary $a,b,c,d\in\mathbb R$ satisfying $ad-bc\neq 0$.

The key observation is that $B^T A B = \begin{pmatrix} a^2 & ab \\ ab & b^2\end{pmatrix}$ does not depend on $c,d$. Therefore $(B^T A B)^\star=B^{-1}A^\star (B^T)^{-1}$ should be independent of $c,d$ as well.

Let $A^\star =\begin{pmatrix} x & y\\ z & w\end{pmatrix}$ for some $x,y,z,w\in\mathbb R$. Then we compute $$B^{-1}A^\star (B^T)^{-1}=\frac 1 {(\operatorname{det} B)^2}\begin{pmatrix} x d^2 - (y+z) cd + w c^2 & -x bd +(yad + zbc) -wac\\ -x bd +(ybc + zad) -wac & x b^2 - (y+z) ab + w a^2 \end{pmatrix}$$.

In case $B=\begin{pmatrix} 1 & 0\\ t & 1\end{pmatrix}$ we get that $B^{-1}A^\star (B^T)^{-1}=\begin{pmatrix} x - (y+z)t + w t^2& \dots\\ \dots & \dots\end{pmatrix}$ is independent of $t$. So $y+z=0$ and $w=0$. Now, in case $B=\begin{pmatrix} 0 & -1\\ 1 & t\end{pmatrix}$ we get $B^{-1}A^\star (B^T)^{-1}=\begin{pmatrix} x t^2 + 0 & \dots\\ \dots & \dots\end{pmatrix}$ from which $x=0$.

This is already a contradiction, because $A^\star=\begin{pmatrix} 0 & y \\ -y & 0\end{pmatrix}$ has either rank 0 or 2. But in case $B=\begin{pmatrix} 1 & 0\\ 0 & t\end{pmatrix}$ we get that $B^{-1}A^\star (B^T)^{-1}=\frac 1 {t^2}\begin{pmatrix} 0 & yt \\ -yt & 0\end{pmatrix}$ is independent of $t$, so $y=0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.